The Correlation between Students English Classroom Speaking Anxiety and Speaking Fluency - Sirat, Rusbihan; Ribahan, Ribahan; Jannah, Miftahul; Assapari, Muhammad Mugni; Addhiny, Tuning Ridha (Program Studi Magister Tadris Bahasa Inggris UIN Sultan Maulana Hasanuddin Banten, 2026)
This study aimed to determine the level of students’ English classroom speaking anxiety, identify the level of students’ speaking fluency, and examine the correlation between English classroom speaking anxiety and speaking fluency among fourth semester students of TBI UIN Mataram. Quantitative correlational design was employed. The participants consisted of 35 fourth semester students. Data were collected using a speaking anxiety questionnaire and a speaking test assessed through a speaking fluency The data were analyzed using descriptive statistics, normality testing, linearity testing, and Pearson Product Moment Correlation through SPSS. The findings showed that the mean score of speaking anxiety was 77.43, indicating a relatively high level of speaking anxiety, while the mean score of speaking fluency was 51.29, indicating a moderate level of speaking fluency. The Pearson correlation analysis revealed that the correlation coefficient -0.767, with a significance value of 0.000 (p < 0.05). This result indicates a strong negative correlation between the two variables. In conclusion, English classroom speaking anxiety has a significant and strong negative relationship with students’ speaking fluency.